Internalization of Ukhuwah Values in Increasing Competitiveness and Social Harmony of Tengger MSMEs - Ramadhani, Kurniawan; S.A, Abdullah; Barmawi, Mohamad; Faizal, Ahmad; Sholihah, Dawimatus; Syirwan, Urfi Ainu (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study explores the internalization of ukhuwah (brotherhood) values in enhancing the competitiveness and social harmony of micro, small, and medium enterprises (MSMEs) within the Tenggerese community in Probolinggo Regency. The values of ukhuwah Islamiyah, wathaniyah, and insaniyah serve as the moral, spiritual, and social foundations that guide entrepreneurial behavior in navigating modern economic challenges. Using a qualitative phenomenological approach, the research collected data through in-depth interviews, participatory observation, and documentation. The findings indicate that the internalization of ukhuwah manifests in three key dimensions: entrepreneurial spirituality, social solidarity, and economic collaboration. MSME actors demonstrate honesty, trust, and mutual cooperation as a distinctive work ethos that strengthens business networks and promotes social cohesion amid market competition. The study concludes that ukhuwah functions not only as a religious doctrine but also as a strategic socio-economic framework rooted in local wisdom and universal human values, contributing to sustainable business development and community resilience.